CENTRIFUGE MODELLING OF THE EVOLUTION OF LOW-ANGLE DETACHMENT FAULTS FROM HIGH-ANGLE NORMAL FAULTS - Koyi H.A.; Skelton A. (My University, 2001)
Centrifuge models composed of a ductile layer overlain by a semi-brittle layer are used to study how deformation localised by a high-angle normal fault promotes detachment faulting. During lateral extension driven by centrifugal force, localised extension along a pre-existing fault initiated localised isostatic upwelling of the denser lower layer. Where the lower ductile layer was significantly less dense than the semi-brittle upper layer, localised extension along the prescribed cut initiated upwelling of the ductile lower layer. Based on model results, we argue that the transition from high-angle normal faulting to low-angle 'detachment' faulting is an inevitable consequence of localising extension, provided that there is viscous coupling between the extending upper layer and the upwelling lower layer. In models with a lower layer of equal density or a denser lower layer, this rotation takes place at the later stages of localised thinning in the upper semi-brittle layer, whereas in models with a less dense lower layer, the rotation takes place earlier due to the buoyant rise of the ductile lower layer.In areas of distributed crustal stretching (e.g. rift basins), where extension of the upper layer is accommodated by numerous steep faults distributed over a wide area and upwelling of lower ductile materials is 'distributed' across the area, normal faults remain more planar despite a large amount of extension. Models show that distributed extension along several closely spaced normal faults encourages rotation of blocks rather than their distortion to form listric faults. We further conclude that the only configuration whereby localisation of extension would not result in detachment-style faulting is when the upper and lower layers were completely decoupled.
Keywords: EXTENSION; LOW-ANGLE DETACHMENT; OCT (OCEAN-CONTINENT TRANSITION ZONE); CENTRIFUGE MODELS